Evaluación del potencial aprovechable de los fluidos geotérmicos y otras consideraciones de importancia. - Bolaños Valiente, Nilda Celina; Castañeda López, Carmen Aída; Marcía Rosales, Sandra Elizabeth; Moreira Olmedo, Laura lzabel (2023)
16102739